Demonstration of bone marrow derived cells in synovial lining by means of giant intracellular granules as genetic markers. Issue 2 (April 1982) - Edwards, J C; Willoughby, D A
Abstract : Beige mice carry a gene (bg) which codes for the presence of giant intracellular granules in a variety of cell types. Bone marrow from beige mice was transplanted into irradiated normal mice. Giant granules similar to those seen in beige mouse synovial cells were observed subsequently in the synovial lining cells of marrow recipients, indicating an influx of bone marrow derived cells into the synovial lining. Giant granule bearing cells also appeared in the subintima. On electron microscopy giant granules have been demonstrated only in macrophage-like or type A cells in marrow recipient synovia, despite the occurrence of giant granules in both type A and type B lining cells in donor material (beige). This tends to suggest that only the type A lining cells are derived from bone marrow, as might be expected from their similarity to mononuclear phagocytes elsewhere. However, the possibility remains that type B cells are also derived from bone marrow but have a slower rate of replacement.